Sex‐Dependent Phenotypic Variability of an SCN5A Mutation: Brugada Syndrome and Sick Sinus Syndrome - Yoshiyasu Aizawa; Taishi Fujisawa; Yoshinori Katsumata; Shun Kohsaka; Akira Kunitomi; Seiko Ohno; Keiko Sonoda; Hidemori Hayashi; Rintaro Hojo; Seiji Fukamizu; Satoshi Nagase; Shogo Ito; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Brugada syndrome (BS) is known to be 9 times more prevalent in males than females. However, little is known about the development of sick sinus syndrome in female members with familial BS. Methods and Results Familial BS patients and family members, both from our institutions and collaborating sites that specialize in clinical care of BS, participated in this study. We collected information on their clinical and genetic background, along with the inheritance patterns of BS. Detailed information on each case with familial BS is described. A total of 7 families, including 25 BS patients (12 females and 13 males), were included. Seven were probands and 18 were family members. Ten out of the 12 female patients and none of the 13 male patients developed sick sinus syndrome. Sudden death or spontaneous ventricular fibrillation occurred in 7 out of 13 male patients and 2 out of 12 female patients. Conclusions Familial BS existed in which female patients developed sick sinus syndrome but male patients did not. Some of those female patients with sick sinus syndrome had unrecognized BS. Information should be collected not only regarding a family history of sudden death or BS, but also whether a pacemaker was implanted in female members.